Biopolitics After Truth Knowledge, Power and Democratic Life - Prozorov, Sergei (Edinburgh University Press, 2021)
Sergei Prozorov contends that the post-truth ideology leads to the degradation of the public sphere that is essential to democratic governance. He argues instead for a positive role of truth-telling in the democratisation of biopolitical governance.